2016
DOI: 10.1016/j.fgb.2015.12.005
|View full text |Cite
|
Sign up to set email alerts
|

A RALDH-like enzyme involved in Fusarium verticillioides development

Abstract: Please cite this article as: Díaz-Sánchez, V., Carmen Limón, M., Schaub, P., Babili, S.A., Avalos, J., A RALDHlike enzyme involved in Fusarium verticillioides development, Fungal Genetics and Biology (2015), doi: http:// dx.doi.org/10. 1016/j.fgb.2015.12.005 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…The Fusarium genomes contain a gene for an aldehyde dehydrogenase highly similar to RALDH enzymes converting retinal to retinoic acid in mammals. This enzyme, that was called CarY, was investigated in F. verticillioides and found to exhibit such enzymatic activity in vitro [ 41 ]. Targeted mutation of the carY gene in F. verticillioides had no effect on carotenogenesis, but resulted in diverse developmental alterations.…”
Section: Genes and Enzymes Of Carotenoid Metabolism In Fmentioning
confidence: 99%
“…The Fusarium genomes contain a gene for an aldehyde dehydrogenase highly similar to RALDH enzymes converting retinal to retinoic acid in mammals. This enzyme, that was called CarY, was investigated in F. verticillioides and found to exhibit such enzymatic activity in vitro [ 41 ]. Targeted mutation of the carY gene in F. verticillioides had no effect on carotenogenesis, but resulted in diverse developmental alterations.…”
Section: Genes and Enzymes Of Carotenoid Metabolism In Fmentioning
confidence: 99%
“…Five different ADHs, ADHComp11367 (accession number KU577907) (Q9LLR2, W8SQV6 and M8AU02), ADHComp3898 (accession number KU577905) (A0A061E1Z5, A0A0B2PSM8, Q8RVW2 and W9RMTS), ADHComp54788 (accession number KU577904) (A0A059BY89 and I1QYB5), ADHComp20158 (accession number KU577906) (K9N4H5) and ADHComp2946 (accession number KU577903) (A0A072TS23 and Q9LRI6), were identified. Phylogenetic analyses revealed that one ADH ( ADHComp54788 ) was closely related to carD , involved in the conversion of β-apo-4′-carotenal in β-apo-4′-carotenol [ 30 ], and showed its highest expression levels at anthesis, while the four others ADHs were more closely related to retinal aldehyde dehydrogenases [ 31 , 32 ], being ADHComp11367 and ADHComp2946 with the highest expression level at anthesis stage, whereas ADHComp3898 and ADHComp20158 at orange and white stages, respectively ( Figure S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Carotenoids were extracted and analyzed as previously described [ 18 , 19 ]. Briefly, carotenoids were extracted with acetone from freeze dried mycelia and were separated by thin layer chromatography developed in light petroleum/diethyl ether/acetone (4:1:1; v/v/v).…”
Section: Methodsmentioning
confidence: 99%